Effect of Steel Fibers and Iron Filings on Concrete Properties with Partial Replacement of Cement by Fly Ash - Zainab A. Mohammed; Assel Qaddoori Makhool; Yasir W. Abdujaleel; Ishraq Hameed Naser; Gummadi Chiranjeevi (Journal of Techniques)
Concrete is one of the most used construction materials., Mineral admixtures with pozzolanic characteristics, like silica fume, fly ash, ground granulated blast-furnace slag, and metakaolin, are often used to replace Portland cement in construction projects partially. Concrete faces persistent challenges, such as low tensile strength, brittleness, and a propensity to crack. This comprehensive study explores the improvement of partial substitution of Portland cement concrete properties with fly ash and reinforced with steel fibers and iron filings. In total, 45 cubes (150 mm) and prisms (100x100x500 mm) were tested using an M25 mix, varying the steel fiber volume fractions at 0%, 0.5%, and 1.0%. These specimens were subjected to given curing periods, after which compressive and split tensile strength tests were conducted to assess their performance. For comparison, plain concrete specimens of the same mix were also tested. Also, iron filings were incorporated into the concrete mix at three different percentages (0%, 0.5%, and 1%) to assess their influence on compressive and tensile strengths after 28 days. The results demonstrate that the addition of steel fibers significantly enhances the mechanical properties of concrete. After 28 days, compressive strength increased by 8.5% to 24%, tensile strength improved by 15% to 49.43%, and flexural strength increased by 38.5% to 85%. Similarly, the inclusion of iron filings improved compressive strength by 9.78% initially, followed by a decrease of 13.84% at higher content. Tensile strength increased by 24.05% to 34.43%, while flexural strength improved by 21% to 29.7%. However, both steel fibers and iron filings slightly reduced workability, with slump values ranging from 63 mm to 92 mm depending on the material and its proportion. The outcomes provide a comparative analysis of the effect of steel fibers and iron filings on the mechanical characteristics of concrete, and present valuable understandings for optimizing concrete behavior in construction applications.